Design fundamental technologies self-latching MEMS optical switch with moving polymer waveguides - Liu, Haobing (2008)
This research deals with some innovative technologies in MEMS (Micro Electro Mechanical Systems) and a novel optical switch based on them. A micro self-latching bi-stable actuator which is based on two innovative structures: a Fork Hinge structure, and a pre-compressed micro spring, is introduced in this work. We improved the optical MEMS technology by using computational optimized polymer waveguides and moving the waveguides. An optical switch used for optical communication is introduced as one of the important applications of these technologies. It provides expandable 2?2 switching capability, which is the first in waveguide based optical switches, and many inherent merits. Some new MEMS process technologies have been invented for the micro fabrication of the switch, including layout controlled one-step dry etch and release of MEMS using deep RIE on SOI wafer, and a method to build silicon-polymer hybrid structure by silicon-polymer bonding. The design, optimization, fabrication, electromechanical and optical characterization of the switch are clarified in the thesis, and the background, content and applications of our new technologies are also detailed in suitable chapters.